The Level of Tennis Skills Among FIK Students as Determined by Their Height - Saleh, M. Sahib; Saleh, Muh. Syahrul; Syafir, Muhammad Isnawan; Syahruddin , Syahruddin; Kamaruddin, Ilham (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
A This study aims to describe the level of tennis playing skills among students of the Department of Physical Education, Health, and Recreation (PJKR) at the Faculty of Sports and Health Sciences, Makassar State University (FIK UNM), specifically focusing on the basic techniques of the forehand drive and backhand drive. It also seeks to analyze the relationship between these skills and students' height. The research adopts a quantitative approach with a descriptive method. The subjects of the study were 30 male PJKR students from FIK UNM who had completed the Tennis course, selected through purposive sampling. To assess the students' forehand and backhand skills, the Hewitt Tennis Test was used. Data were analyzed using descriptive and inferential statistics. The results showed that students' forehand drive skills (mean score: 20.60) were better than their backhand drive skills (mean score: 14.57). The majority of students demonstrated a